أثر القراءات القرآنية في ترجيح الخلاف النحوي عند الطبري في تفسيره -نماذج مختارة - غربي, هاجر; سنوس, إيمان; قرميط, أسماء (My University, 2019)
يهدف هذا البحث إلى بيان أثر القراءات القرآنية على تفسير القرآن الكريم عند الإمام الطبري  وخاصة فيما يتعلق في المسائل النحوية الواردة فيه، كما أن البحث يركز على توظيف الطبري للقراءات والاستعانة بها في تفسيره، وموقفه منها توجيها وإعرابا وبيان مدى أثرها في ت رجيح الخلاف الواقع بين النحويين، ولدراسة هذا الموضوع قسمنا العمل إلى مقدمة: بينا فيها منهجنا في العمل، ثم مبحث أول: تمثل في المدخل التمهيدي للموضوع، ثم مبحث ثاني: تمثل في الدراسة النظرية، ثم المبحث الثالث: والمتمثل في الدراسة التطبيقية، وذلك بذكر نماذج مختارة، وفي الأخير ختمنا بحثنا بجملة من النتائج التي توصلنا إليها، ومن أهمها: بيان مدى أثر القراءات القرآنية وتوظيفها في ترجيح الخلاف النحوي، مع ذكر بعض الوصايا. Summary This research aims to show the effect of Coranic readings on the interpretation of Holy Coran for Imam Al Tabaree, especially concerning grammatical aspects which appear in it. This research also focused on the use of Imam Al Tabaree of these readings and the help of interpretation, as well as his position in orientation and analysis, and how much effect it has on the conflict that occurs between grammatician. To study this subject, we divided our work to an introduction in which we showed our methodology. After that, the first section which represents an introductory approach to the subject. Then, the second section which represents the theorical study. Finally, the third section which represents the practical aspect by pointing out some chosen samples. We concluded our research with a serie of results with mentioning some recommendations.
لغة